Strategi Pengembangan Usaha Kuliner Sibolang Durian di Medan, Sumatera Utara - GINTING, CLOUDIA BR; ANTARA, MADE; WIBAWA, MADE SATRIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Sibolang Durian Culinary Business Development Strategy in Medan, North Sumatera.  Sibolang Durian is one of the companies engaged in marketing local durians in Medan, North Sumatra. The purpose of this study is to formulate general strategies, alternative strategies, priority strategies. As for some obstacles in the Sibolang Durian culinary business in Medan, North Sumatra caused the need for strategy formulation with the aim of identifying internal and external factors that became strengths, weaknesses, opportunities and threats, then formulating general strategies, alternative strategies, priority strategies, which are right to be implemented in the Sibolang Durian culinary business in Medan, North Sumatra. This research uses qualitative and quantitative research methods. The strategy formulation process is carried out through IE matrix analysis (IFAS-EFAS), SWOT matrix and QSPM matrix. Sibolang Durian development strategy can apply a general strategy, namely an intensive strategy (market penetration, market development and product development). Based on the results of the SWOT matrix analysis, there are eleven alternative strategies that can be developed through SO, WO, ST, WT strategies. The main priority strategy obtained from the results of the analysis using the QSPM matrix, the Sibolang Durian culinary business in Medan, North Sumatra is high market demand by utilizing a lot of durian demand in developing durian business innovations so that it can meet consumer tastes with a TAS score of 19.38.